Analisis Pengaruh Kemudahan, Efisiensi, dan Reliability Penggunaan terhadap Minat Penggunaan Media Chatbot Sebagai Sarana dalam Pemasaran Digital (Studi Kasus Pedagang E-Commerce) - Fadilah, Muhamad Rafli; Nuriyah, Aminah (Universitas Batanghari Jambi, 2024)
This research aims to analyze the direct influence of the variables ease of use, efficiency and reliability of use on interest in using chatbot media as a means of digital marketing. This research is quantitative research. The type of data used is primary data obtained through a questionnaire that was distributed to a total of 199 respondents and secondary data obtained from literature related to the problems studied. The data analysis technique used is descriptive statistics and Structural Equation Modeling (SEM) analysis with the Partial Least Square (PLS) method, all data of which will be processed in the Smartpls 4 application. The results of this study found that there is a positive and significant influence between the ease of use variable on interest in use, then the variable efficiency of use on interest in use and the positive and insignificant influence between the variable reliability of use on interest in using chatbot media as a means of digital marketing